High-specific-surface-area high-nitrogen-oxygen-doped lignin porous carbon material as well as preparation method and application thereof

By assembling lignin and magnesium hydroxide and melamine/melamine to form a four -format super molecular complex, and optimize the structure in the process of carbonization and activation, prepare high -ratio high nitrogen oxygen doped woody porous carbon materials The problem of irrational material structure in the existing technology has been solved, and the electrochemical performance of zinc ion hybrid electric containers has been significantly improved.

CN119370824AActive Publication Date: 2025-01-28SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411378041.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-28
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The prior art is difficult to take into account both high specific surface area, high proportion of micromesoporous structure, high nitrogen oxygen content and ordered nanostructures, resulting in low active site utilization and slow ion transfer rate of zinc ion hybrid capacitors.

Method used

Four -set super molecular complexes were assembled through lignin and magnesium hydroxide and melamine/melamine, and carbonized in an inert gas atmosphere. Then use weak corrosive potassium salts to activate it to prepare a high -ratio surface area of ​​high nitrogen oxygen. Miscellaneous porous carbon material.

Benefits of technology

The high-ratio surface area, rich micro-media structure, and high nitrogen-hydated doping amount significantly improved the ratio capacitance and electrochemical properties of zinc ion hybrid containers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370824A_ABST
    Figure CN119370824A_ABST
Patent Text Reader

Abstract

The invention discloses a high-specific-surface-area high-nitrogen-oxygen-doped lignin porous carbon material as well as a preparation method and application thereof. The method comprises the following steps: firstly, preparing a supramolecular compound from lignin, magnesium hydroxide, cyanuric acid and melamine through solvothermal reaction, then directly carbonizing to obtain a nitrogen-doped lignin carbon / magnesium oxide compound, and activating the nitrogen-doped lignin carbon / magnesium oxide compound by using weakly corrosive sylvite to increase a micro-mesoporous structure. Therefore, the nitrogen and oxygen doped lignin porous carbon material with ultrahigh specific surface area and rich micro-mesopores is prepared. According to the obtained lignin porous carbon material with the high specific surface area and high nitrogen and oxygen doping, a large number of active sites can be provided due to the high specific surface area, wettability of the carbon material can be improved due to high nitrogen and oxygen doping, the utilization rate of the active sites is increased, and the problem that the pore diameter of the carbon material is not matched with a current carrier is solved due to the rich micro-mesoporous structure; and the specific capacitance of the zinc ion hybrid capacitor is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of positive electrode materials for zinc ion hybrid capacitors, and particularly relates to a high specific surface area and high nitrogen and oxygen doped lignin porous carbon material, and a preparation method thereof and an application thereof in zinc ion hybrid capacitors. Background Art

[0002] The metal zinc anode has high theoretical specific capacity (820 mAh / g), low redox potential (-0.76 V vs. SHE), and environmental friendliness, showing good application potential in the field of large-scale energy storage. Carbon materials have the characteristics of high specific surface area, excellent conductivity, stable physicochemical properties, and adjustable pore structure. Therefore, zinc ion hybrid capacitors composed of metal zinc anode and porous carbon cathode materials have attracted widespread attention due to their high energy density and high power density. However, the low zinc storage capacity of porous carbon materials is difficult to match the high-capacity zinc anode. There are two key issues that need to be solved to improve the zinc storage capacity of porous carbon materials: (1) poor interface wettability leads to low utilization of active sites; (2) mismatch between pore size and carrier leads to slow ion transfer rate.

[0003] In recent years, in response to the above two problems, researchers have mainly optimized the electrochemical properties of carbon materials through the following three strategies: (1) heteroatom doping. Heteroatoms can improve the intrinsic properties of carbon materials (conductivity and wettability), help regulate the microenvironment of the carbon surface, enhance the accessibility of active sites and provide additional pseudocapacitance; (2) pore structure regulation. Micropores with pore diameters larger than the carrier diameter can contribute more active surfaces and provide a large number of zinc storage active sites. Mesopores serve as ion mass transfer channels and help accelerate ion transport; (3) nanostructure design. Compared with zero-dimensional, one-dimensional and three-dimensional nanostructures, two-dimensional nanosheets help accelerate the transfer of electrons, shorten the ion transport path, and fully expose active sites. Therefore, the preparation of high specific surface area heteroatom-doped porous carbon materials through heteroatom doping, pore structure regulation and nanostructure design strategies is an effective method to improve the performance of zinc ion hybrid capacitors.

[0004] In terms of heteroatom doping, nitrogen and oxygen atoms are the most widely studied. Since porous carbon materials are prepared by carbonization activation at relatively low temperatures, there must be oxygen functional groups on the surface of the carbon materials, and oxygen functional groups can provide additional pseudocapacitive active sites to improve the specific capacity. The atomic radius of nitrogen is similar to that of carbon atoms and is easy to dope. In addition, the electronegativity of nitrogen atoms (3.04) is large, which can change the electronic structure and charge distribution of carbon materials, which is beneficial to reduce the adsorption energy barrier between carbon-oxygen bonds and zinc ions. For example, Zheng et al. (Chemical Engineering Journal, 2020, 387, 124161) obtained oxygen-rich doped porous carbon materials (specific surface area: 523 m2) by burning the solvent thermal reaction products of sodium and ethanol and treating them with concentrated nitric acid. 2 / g, oxygen content: 19.87 at%), and the specific capacity at a current density of 0.5 A / g is 132.7 mAh / g, which is significantly higher than that of undoped porous carbon materials (82.9 mAh / g). However, due to the low specific surface area and underdeveloped pore structure, the assembled zinc ion hybrid capacitor has poor performance. Liu et al. (Nano Research, 2019, 12, 2835–2841) mixed chitosan, potassium bicarbonate and ferric nitrate in an aqueous solution, dried and directly carbonized to obtain nitrogen-doped hierarchical porous carbon materials (specific surface area: 879 m 2 / g, oxygen content: 8.2 at%, nitrogen content: 5.3 at.%), the specific capacity at a current density of 0.1 A / g is 136.8 mAh / g, which is higher than that of undoped carbon materials. This process achieves a higher doping level, but the specific surface area is lower, resulting in a lower specific capacity of the zinc ion hybrid capacitor.

[0005] In terms of pore structure regulation, the compatibility of pore size and carriers is directly related to the storage and transport of zinc ions. 2+ , with a diameter of 0.86 nm) is the main carrier in the charge storage process. When the micropore diameter is greater than 0.86 nm, it is beneficial to improve the accessibility of solvated ions, and the mesopores help accelerate the transport of ions and achieve the best zinc storage capacity. For example, Wang et al. (Advanced Materials, 2022, 34, 2203744.) used potassium hydroxide to secondary activate ZIF-8 (metal organic framework) derived carbon materials to prepare high specific surface area nitrogen-doped hierarchical porous carbon (specific surface area: 3553m 2 / g, microporosity: 20.0%, mesoporosity: 72.6%, nitrogen content: 2.67 at.%, oxygen content: 7.48 at.%), and exhibited a specific capacity of up to 199.1 mAh / g at a current density of 0.5 A / g. However, the process uses a highly corrosive activator, which leads to severe loss of nitrogen species, and ZIF-8 is prepared from synthetic chemicals, which is too expensive to be conducive to industrial production. An et al. (Applied Surface Science, 2020, 530, 147220) used polyvinyl pyrrolidone to coat commercial activated carbon and then carbonized it to obtain a mesoporous oxygen-doped carbon material (specific surface area: 2527m 2 / g, microporosity: 49.0%, mesoporosity: 51.0%, oxygen functional group content: 47.0 wt.%), and exhibited a specific capacity of 176.1 mAh / g at a current density of 0.5 A / g. However, the nanostructure of the carbon material prepared by this process showed an irregular block morphology, resulting in a rate performance of only 41% at a current density of 10 A / g.

[0006] In terms of nanostructure design, ordered nanostructures can maximize the advantages of porous carbon materials. In particular, two-dimensional porous carbon nanosheets have high specific surface area and abundant micropores, which can provide abundant interfacial active sites and shorter ion transmission paths, which are beneficial to reduce the resistance of carbon materials and accelerate the diffusion rate of ions. Liu et al. (MaterialsToday Chemistry, 2023, 29, 101476.) freeze-dried and carbonized sugarcane stems, and then activated them with a large amount of potassium hydroxide to prepare high specific surface area nitrogen-oxygen doped carbon nanosheets (specific surface area: 3178 m 2 / g, nitrogen content: 1.48 at.%, oxygen content: 7.58 at.%), with a specific capacity of 198.4 mAh / g at a current density of 0.2 A / g. Zhang et al. (Journal of Colloid and Interface Science, 2024, 6664, 146-155) used polyvinyl pyrrolidone as a carbon source, urea as a nitrogen source, and potassium ferric oxalate as an activator to prepare nitrogen-oxygen doped porous carbon nanosheets (specific surface area: 1843 m 2 / g, nitrogen content: 7.00 at.%, oxygen content 6.00 at.%), with a specific capacity of 181.0 mAh / g at a current density of 0.5 A / g. However, the carbon precursors in the above processes are derived from synthetic chemicals, which are expensive, or involve a large amount of highly corrosive chemical reagents during the preparation process, which is not conducive to industrial production.

[0007] Therefore, renewable and low-cost biomass-derived carbon materials have attracted the attention of researchers. Industrial lignin is a byproduct of the pulp and paper and bioethanol industries. It has the characteristics of high carbon content, rich oxygen-containing functional groups and easy modification, making it an ideal carbon precursor.

[0008] In order to prepare nitrogen-doped lignin porous carbon materials with high specific surface area, the commonly used method is to directly carbonize lignin with nitrogen dopants (urea, thiourea, melamine and cyanuric chloride, etc.) and activators (potassium hydroxide, zinc chloride, potassium oxalate and phosphoric acid, etc.) at high temperature. However, the thermal stability of nitrogen species is poor, making it difficult to prepare highly nitrogen-doped lignin porous carbon materials. For example, Zhu et al. (Chemical Engineering Journal, 2017, 316, 770-777) mixed the lignin black liquor obtained by treating rice straw with potassium hydroxide with melamine and dried it, and then carbonized it at high temperature to prepare nitrogen-doped lignin porous carbon materials (specific surface area: 2646 m 2 / g, microporosity: 45%, nitrogen content: 1.21 at.%, oxygen content: 8.38 at.%), when used in supercapacitors, has a specific capacitance of 337 F / g at a current density of 0.5 A / g. In order to further increase the nitrogen doping amount, Wang et al. (International Journal of Biological Macromolecules, 2024,265, 130796) used cyanuric chloride to modify lignin, directly used it as a carbon and nitrogen source, and used sodium hydroxide as an activator to prepare nitrogen-doped lignin carbon balls (specific surface area: 1778 m 2 / g, pore volume: 0.5 cm 3 / g, nitrogen content: 2.85 at.%), when used in supercapacitors, has a specific capacitance of 473 F / g at a current density of 0.5 A / g. Although the carbon materials prepared by the above technology show excellent performance in supercapacitors, they have low nitrogen doping, less micro-mesopores or low pore volume and cannot be directly used in zinc ion hybrid capacitors.

[0009] In order to improve the performance of lignin porous carbon materials in zinc ion hybrid capacitors, Xue et al. (Chemical Engineering Journal, 2024, 480, 147994) directly pyrolyzed a mixture of lignin, urea and potassium oxalate to prepare nitrogen-oxygen doped lignin porous carbon (specific surface area: 1949 m 2 / g, microporosity: 46%, nitrogen content: 1.64 at.%, oxygen content: 8.42 at.%), with a specific capacitance of 360 F / g at a current density of 0.1 A / g; Li et al. (ACS Applied Energy Materials, 2023, 6, 6700-6711) mixed carbonized lignin, thiourea, urea and three times the amount of potassium hydroxide, and prepared nitrogen / sulfur-doped activated carbon materials (specific surface area: 2773 m 2 / g, microporosity: 57%, nitrogen content: 1.32 at.%, oxygen content: 9.05 at.%), when used in zinc ion hybrid capacitors, has a specific capacity of 121.7 mAh / g at a current density of 0.3 A / g. However, the current technology is to directly mix lignin with activators and (or) dopants to easily form random aggregates, resulting in disordered internal structure of porous carbon materials, fewer micro-mesoporous or low nitrogen doping (<3at.%), and poor electrochemical performance of zinc ion hybrid capacitors.

[0010] Lignin has thermoplastic characteristics, which makes it easy to shrink and aggregate during carbonization. In order to achieve ordered nanostructures and increase mesopores, hard templates such as silica, polystyrene and nanomagnesia are usually added during the preparation of lignin carbon materials. Among them, nanomagnesia has the characteristics of being cheap, easy to obtain and easy to remove, and has attracted the attention of researchers. Song et al. (RSC Advances, 2017, 7, 48324) used F127 to disperse nanomagnesia templates and alkaline lignin, and prepared lignin mesoporous carbon (specific surface area: 712 m2) by solvent evaporation assembly and carbonization. 2 / g, mesoporosity: 83%). A large number of mesopores improve the ion transmission rate, but due to the lack of micropores and low specific surface area, its electrochemical performance in supercapacitors is poor, only 186 F / g. Zhang et al. (Carbon, 2020, 162: 256-266) prepared a flower-shaped lignin mesoporous carbon material composed of two-dimensional nanosheets by evaporation-induced self-assembly and high-temperature carbonization of enzymatic lignin and magnesium hydroxide templates (specific surface area: 827 m 2 / g), and has excellent performance as a photocatalyst carrier. Although magnesium hydroxide is an excellent sheet-structure template and avoids the use of surfactants, the weak activation of magnesium hydroxide leads to a low specific surface area and fewer micropores, and it cannot be directly used in zinc ion hybrid capacitors.

[0011] In addition, in the study of high nitrogen-doped lignin carbon materials, the poor thermal stability of nitrogen dopants and poor compatibility with lignin led to low doping levels. Therefore, Fu et al. (Journal of Energy Storage, 2023, 63, 106947) co-pyrolyzed a complex of sodium lignin sulfonate / zinc oxalate and melamine. Since zinc cyanamide was generated in situ during the pyrolysis process, a large amount of nitrogen species were retained, achieving a higher nitrogen doping level (14.47 at.%). However, the weak etching effect of zinc cyanamide resulted in a specific surface area of ​​only 95 m2 of the prepared nitrogen-doped lignin carbon material. 2 / g, when used as a supercapacitor electrode material, the mass specific capacitance at a current density of 0.5 A / g is only 300 F / g. The high nitrogen-doped carbon material prepared by this process cannot be used in zinc ion capacitors due to its low specific surface area and lack of micropores. Zhang et al. (Nano Energy, 2022, 103, 107827) assembled sodium lignin sulfonate with almost 15 times the amount of melamine-cyanuric acid supramolecular molecules through hydrogen bonds and van der Waals forces and then directly carbonized to prepare high nitrogen-doped lignin carbon materials (nitrogen content: 14.9 at.%, oxygen content: 4.7 at.%). Since no additional activator was added, the specific surface area of ​​the prepared high nitrogen-doped lignin carbon material is only 657 m 2 / g, and fewer micropores (8%), with a specific capacitance of only 266 F / g at a current density of 0.01 A / g. Although pseudocapacitance is introduced by doping with a high ratio of nitrogen / oxygen atoms, it has certain electrochemical properties in zinc ion hybrid capacitors. However, the nitrogen dopant is still mixed with lignin in the form of a guest through physical interactions such as hydrogen bonds. Even if a chemical activator is used to further increase the specific surface area, it may cause a sharp drop in the nitrogen / oxygen doping level during further activation and pore formation.

[0012] In summary, due to the poor compatibility or weak interaction between lignin and templates or dopants, and the large-scale use of highly corrosive activators, the lignin porous carbon nanostructure is disordered, the pore structure distribution is unreasonable, or the doping level is low. The nitrogen-oxygen doped lignin porous carbon materials prepared by the existing technology or process cannot simultaneously take into account high surface area, high proportion of micro-mesoporous structure, high nitrogen-oxygen content and ordered nanostructure, resulting in low utilization of active sites and slow ion transfer rate, making it difficult to use in zinc ion hybrid capacitors. Summary of the invention

[0013] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a high specific surface area and high nitrogen and oxygen doped lignin porous carbon material.

[0014] The method of the present invention utilizes the active functional groups of lignin to assemble a four-component supramolecular complex of lignin / magnesium hydroxide / cyanuric acid / melamine based on hydrogen bonds and chemical bonds, and carbonization and activation are used to prepare a high specific surface area high nitrogen and oxygen doped lignin porous carbon material. First, lignin is adsorbed on the magnesium hydroxide sheet through hydrogen bonding, which is beneficial to inhibit the collapse of the structure during the carbonization process. Then, the phenolic hydroxyl group of lignin undergoes a cross-linking reaction with cyanuric chloride, and further assembles with melamine under solvent thermal conditions based on hydrogen bonds to form a four-component supramolecular complex of magnesium hydroxide / lignin / cyanuric acid / melamine and directly carbonizes to obtain a nitrogen-doped lignin carbon / magnesium oxide complex, which can avoid the large-scale loss of nitrogen atoms during the carbonization process. Finally, the nitrogen-doped lignin carbon / magnesium oxide complex is activated by a weakly corrosive potassium salt to increase the micro-mesoporous structure, thereby preparing a lignin porous carbon material with ultra-high specific surface area, rich micro-mesoporous and nitrogen-oxygen doped.

[0015] Another object of the present invention is to provide a high specific surface area and high nitrogen and oxygen doped lignin porous carbon material prepared by the above method. The high specific surface area can provide a large number of active sites, and the high nitrogen and oxygen doping can improve the wettability of the carbon material and increase the utilization rate of the active sites. The rich micro-mesoporous structure improves the problem of pore size and carrier mismatch of the carbon material, thereby significantly improving the specific capacitance of the zinc ion hybrid capacitor.

[0016] The high specific surface area and high nitrogen and oxygen doped lignin porous carbon material prepared by the present invention has the morphology of interconnected two-dimensional nanosheets and a specific surface area of ​​more than 2500 m 2 / g, the nitrogen and oxygen atomic content is 13.0 at.% (nitrogen content: 5.0 at.%, oxygen content: 8.0 at.%), and the volume proportion of micro-mesopores is greater than 85%.

[0017] Another object of the present invention is to provide the application of the above-mentioned high specific surface area nitrogen and oxygen doped lignin carbon material in zinc ion hybrid capacitors.

[0018] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a high specific surface area high nitrogen and oxygen doped lignin porous carbon material comprises the following steps: (1) dissolving lignin in ethanol, adding magnesium hydroxide nanosheets, and stirring to obtain a lignin / magnesium hydroxide mixed solution; (2) adding an excess of cyanuric chloride to the lignin / magnesium hydroxide mixture to react, then adding melamine to carry out a solvothermal reaction, filtering and drying to obtain a four-component supramolecular complex of lignin / magnesium hydroxide / cyanuric acid / melamine; (3) carbonizing the four-component supramolecular complex of lignin / magnesium hydroxide / cyanuric acid / melamine under an inert gas atmosphere to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide complex; (4) After the nitrogen-oxygen doped lignin carbon / magnesium oxide composite and the weakly corrosive potassium salt are evenly mixed, the mixture is activated in an inert gas atmosphere, acid-washed, filtered and dried to obtain a high specific surface area and high nitrogen-oxygen doped lignin porous carbon material.

[0019] Preferably, the magnesium hydroxide nanosheets in step (1) are obtained by the following method: dispersing nano-magnesium oxide in water, heating and hydrolyzing, filtering and drying to obtain magnesium hydroxide nanosheets.

[0020] More preferably, the particle size of the nano magnesium oxide is 10 to 100 nm.

[0021] More preferably, the mass ratio of the nano-magnesium oxide to water is 1:10 to 30; further preferably, it is 1:10 to 14.5.

[0022] More preferably, the temperature of the heating hydrolysis is 70-90°C, and the time is 2-4 h; further preferably, the temperature of the heating hydrolysis is 70-80°C, and the time is 3-4 h.

[0023] Preferably, the lignin in step (1) is at least one of enzymatic lignin produced as a byproduct of the bioethanol industry, alkali lignin in black liquor from alkaline pulping, and organic solvent lignin.

[0024] Preferably, the ratio of lignin, ethanol and magnesium hydroxide nanosheets in step (1) is 10 g: 200-300 mL: 10-30 g; more preferably, it is 10 g: 200-300 mL: 10-20 g.

[0025] Preferably, the stirring time in step (1) is 3 to 5 h; more preferably, it is 3 to 4 h.

[0026] Preferably, the mass ratio of the cyanuric chloride and melamine in step (2) to the lignin in step (1) is 10-20:5-15:10; more preferably, it is 10-20:7-15:10; and more preferably, it is 10-15:7-10:10.

[0027] Preferably, the temperature for reacting the cyanuric chloride in step (2) is 0 to 5°C and the reaction time is 20 to 40 minutes; more preferably 20 to 30 minutes.

[0028] Preferably, the temperature of adding melamine for the solvothermal reaction in step (2) is 140-180°C, and the time is 8-12 h; further preferably, the temperature is 140-160°C, and the time is 10-12 h.

[0029] Preferably, the inert gas in step (3) is at least one of a rare gas and nitrogen; more preferably at least one of nitrogen, argon and helium.

[0030] Preferably, the carbonization temperature in step (3) is 500-600°C, and the time is 1-3 h; further preferably, the temperature is 550-600°C, and the time is 1-2 h.

[0031] Preferably, the heating rate of the carbonization in step (3) is 5 to 10 °C / min.

[0032] Preferably, the weakly corrosive potassium salt in step (4) is at least one of potassium bicarbonate, potassium acetate and potassium citrate.

[0033] Preferably, in step (4), the mass ratio of the nitrogen-oxygen doped lignin carbon / magnesium oxide composite to the weakly corrosive potassium salt is 1:0.5-1.5; more preferably, it is 1:0.5-1.

[0034] Preferably, the activation temperature in step (4) is 600-800°C, and the time is 1-3 h; further preferably, the temperature is 700-800°C, and the time is 1-2 h.

[0035] Preferably, the activation heating rate in step (4) is 5 to 10 °C / min.

[0036] Preferably, the inert gas in step (4) is at least one of a rare gas and nitrogen; more preferably at least one of nitrogen, argon and helium.

[0037] Preferably, the acid solution used for pickling in step (4) is a 0.5-1.5 mol / L hydrochloric acid solution or a sulfuric acid solution, and the soaking and washing time is 8-12 h.

[0038] Preferably, the acid washing in step (4) is followed by water washing, filtering and drying.

[0039] Preferably, the drying in steps (2) and (4) includes one of forced air drying, vacuum drying, infrared drying and freeze drying; the drying temperature is 80 to 120° C., more preferably 100° C., and the drying time is 24 h.

[0040] A high specific surface area, high nitrogen and oxygen, nitrogen and oxygen doped lignin porous carbon material prepared by the above method.

[0041] The high specific surface area high nitrogen and oxygen doped lignin porous carbon material prepared by the method of the present invention has a specific surface area range of 2500 to 3000 m 2 / g, the pore size is 0.4-100 nm, the micro-mesoporosity is greater than 85%, and the nitrogen and oxygen atom content is greater than 13.0 at.% (nitrogen content is greater than 5.0 at.%, and oxygen content is greater than 8.0 at.%).

[0042] The application of the above-mentioned high specific surface area and high nitrogen and oxygen doped lignin porous carbon material in zinc ion hybrid capacitors.

[0043] This patent will be described in more detail below.

[0044] (1) Disperse nano-magnesium oxide in water, heat and hydrolyze, filter and dry to obtain magnesium hydroxide nanosheets: The purpose of this step is to fully hydrolyze nano-magnesium oxide to obtain magnesium hydroxide. Unlike magnesium oxide, magnesium hydroxide has a large number of hydroxyl functional groups on its surface, which can easily form hydrogen bonds with oxygen-containing functional groups (hydroxyl, phenolic hydroxyl and carboxyl groups, etc.) of lignin for self-assembly, and can improve the compatibility of lignin with the magnesium hydroxide template. In addition, the magnesium hydroxide obtained by hydrolysis of nano-magnesium oxide has a two-dimensional sheet structure, which plays a structural guiding and space occupying role in the pyrolysis and carbonization process, and is conducive to the formation of a sheet-shaped mesoporous structure.

[0045] The hydrolysis temperature in this step is between 70 and 90 °C, and the holding time is controlled within 2 to 4 hours to allow the magnesium oxide to be fully hydrolyzed. If the hydrolysis temperature is too low, the magnesium oxide will not be fully hydrolyzed and will take a long time. If the hydrolysis temperature is between 90 and 110 °C, the holding time is controlled between 2 and 3 hours to avoid too fast evaporation of water, which is not conducive to hydrolysis.

[0046] (2) Dissolve lignin in ethanol, add magnesium hydroxide nanosheets, and stir to obtain a lignin / magnesium hydroxide mixed solution: The lignin in this step is enzymatic lignin soluble in ethanol or other lignin soluble in ethanol. The purpose is that the lignin soluble in ethanol has a smaller molecular weight and contains more oxygen functional groups, which is conducive to enhancing the interaction with the magnesium hydroxide template. The solvent described in step (2) is ethanol, which is used to dissolve lignin on the one hand to enhance the reaction activity of lignin with cyanuric chloride in step (3), and on the other hand to react with cyanuric chloride to generate cyanate groups. If the solubility of lignin in the solvent is poor, it is easy to aggregate, which will not only lead to uneven composite of lignin and magnesium hydroxide, but also reduce the reaction activity of lignin with cyanuric chloride, affecting the nitrogen doping effect of the prepared carbon material.

[0047] If the amount of ethanol used in this step is too low, the lignin will not be fully dissolved and will not be evenly compounded with magnesium hydroxide; if the amount of ethanol used is too high, the concentration of lignin will be reduced, which is not conducive to the cross-linking reaction with cyanuric chloride. If the mass ratio of magnesium hydroxide is too low, too little magnesium oxide will be decomposed and formed during the carbonization process of step (4), resulting in too low specific surface area of ​​the product and lack of mesoporous structure, which is not conducive to further activation in step (5) to produce micro-mesoporous structure; if the mass ratio of magnesium hydroxide is too high, more water vapor and magnesium oxide will be decomposed and generated during the carbonization process of step (4), resulting in too much and unstable mesoporous structure, which is not conducive to further activation in step (5).

[0048] (3) Add cyanuric chloride to the lignin / magnesium hydroxide mixture to react, then add melamine to react, filter and dry to obtain a four-component supramolecular complex of lignin / magnesium hydroxide / cyanuric acid / melamine: In this step, cyanuric chloride reacts with lignin adsorbed on the surface of magnesium hydroxide and ethanol solvent at 0°C, and then is grafted onto the surface of lignin to form lignin / magnesium hydroxide / cyanuric acid. In order to ensure that lignin and cyanuric chloride react fully, cyanuric chloride needs to be added in excess. The reaction temperature is controlled at 0-5°C because at this temperature, cyanuric chloride will undergo a single substitution reaction of one chlorine atom with the phenolic hydroxyl group, and the other two chlorine atoms will react with the solvent (ethanol) to form cyanate groups, which is more conducive to the formation of supramolecular structure.

[0049] In this step, too much or too little melamine is not conducive to the condensation of supramolecules during the solvothermal reaction to form supramolecules. Melamine cannot be dissolved in ethanol, and it needs to be fully stirred after adding melamine. If the melamine is not evenly dispersed, it is not conducive to further solvothermal reaction.

[0050] The solvent thermal reaction temperature in this step is 140-180 °C and the time is 8-12 h. If the temperature is too low or the time is too short, it is not conducive to the condensation of supramolecular; if the temperature is too high or the time is too long, it will cause lignin degradation and the yield will be too low.

[0051] (4) Carbonizing the four-component supramolecular complex of lignin / magnesium hydroxide / cyanuric acid / melamine under an inert gas atmosphere to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide complex: The carbonization in this step needs to be carried out in a nitrogen, argon or other inert gas atmosphere. The carbonization temperature is set between 500 and 600 °C, the heating rate is 5 to 10 °C / min, and the temperature is kept for 1 to 3 hours. If the temperature is too low and the time is too short, the magnesium hydroxide will not be completely decomposed and the carbonization will be incomplete; if the temperature is too high and the time is too long, the nitrogen species will be decomposed and the production cost will increase.

[0052] (5) After uniformly mixing the nitrogen-oxygen doped lignin carbon / magnesium oxide composite and the weakly corrosive potassium salt, the composite is activated, washed, filtered and dried in an inert gas atmosphere to obtain a high specific surface area and high nitrogen-oxygen doped lignin porous carbon material: The carbonization in this step needs to be carried out in a nitrogen, argon or other inert gas atmosphere. The carbonization temperature is set between 600 and 800 °C, the heating rate is 5 to 10 °C / min, and the insulation time is 1 to 3 hours. If the quality of potassium bicarbonate is too low, the carbonization temperature is too low, and the insulation time is too short, it will lead to the activation effect of potassium bicarbonate being not conducive to exerting the product pore structure is underdeveloped and the specific surface area is too low; if the quality of potassium bicarbonate is too high, the carbonization temperature is too high, and the insulation time is too long, the pore structure will be destroyed due to excessive activation, the production cost will increase, and the yield of carbon products will decrease.

[0053] The concentration of the dilute acid solution used for washing in this step is required to be 0.5-1.5 mol / L, and the immersion time is controlled at 6-12 h. If the acid concentration is too low or the immersion time is too short, oxide residues will remain and the specific surface area of ​​the product will be reduced; if the acid concentration is too high or the immersion time is too long, the pore structure of the product will be destroyed.

[0054] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The high specific surface area and high nitrogen and oxygen doped lignin porous carbon material prepared by the present invention has a high specific surface area, an ordered nanosheet structure, a high micro-mesoporosis, and a high nitrogen and oxygen doping amount. The micro-mesopores in the nanosheet structure can provide abundant active sites and fast ion transport pathways, and the nitrogen and oxygen functional groups can promote the accessibility of the active sites, thereby improving the utilization of the active sites. As a positive electrode material for zinc ion hybrid capacitors, it has a higher specific capacitance and shows good application prospects.

[0055] (2) In the preparation method of the present invention, lignin is assembled through hydrogen bonds and chemical bonds to obtain a four-component supramolecular complex of lignin / magnesium hydroxide / cyanuric acid / melamine, which effectively improves the compatibility between lignin and the template and nitrogen source, and uses a weakly corrosive potassium salt activator to achieve efficient activation and pore formation. In addition, industrial lignin is used as a carbon source, which has abundant reserves, low cost, and is renewable, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 This is the Fourier infrared spectrum of cyanuric chloride grafted onto lignin in Example 1 of the present invention.

[0057] Figure 2 This is a scanning electron microscope image of the high specific surface area and high nitrogen and oxygen doped lignin porous carbon material obtained in Example 1 of the present invention.

[0058] Figure 3This is a transmission electron microscope image of the high specific surface area and high nitrogen and oxygen doped lignin porous carbon material obtained in Example 1 of the present invention.

[0059] Figure 4 It is the nitrogen adsorption / desorption isotherm and pore size distribution curve of the high specific surface area and high nitrogen and oxygen doped lignin porous carbon material obtained in Example 1 of the present invention.

[0060] Figure 5 This is the constant current charge and discharge curve of the high specific surface area and high nitrogen and oxygen doped lignin porous carbon material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0061] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0062] Unless otherwise specified, the reagents used in the examples can be purchased from the market.

[0063] Example 1 Weigh 13.8 g of nano-magnesium oxide (particle size of about 50 nm) and add it to 150 mL of deionized water. Stir and hydrolyze it at 80 °C for 3 h. After cooling to room temperature, filter it, and then transfer the product to a 100 °C forced air drying oven and dry it for 24 h to obtain 20 g of magnesium hydroxide nanosheets. Take 10 g of enzymatic lignin, dissolve it in 300 mL of ethanol, add the 20 g of magnesium hydroxide nanosheets prepared above, and stir it at room temperature for 4 h to obtain a lignin / magnesium hydroxide mixed solution. 15 g of cyanuric chloride was weighed and added to the above lignin / magnesium hydroxide mixture. After reacting at 0°C for 30 min, 10 g of melamine was added, stirred evenly at room temperature, transferred to a reactor, reacted at 160°C for 10 h, cooled to room temperature, filtered, and then the product was transferred to a 100°C forced air drying oven and dried for 24 h to obtain a four-component supramolecular complex of lignin / magnesium hydroxide / cyanuric acid / melamine. The composite powder was placed in a tube furnace and carbonized in a nitrogen atmosphere. The temperature was raised from room temperature to 550 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature was lowered to room temperature to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide composite. Weigh 1 g of nitrogen-oxygen-doped lignin carbon / magnesium oxide composite and 1 g of potassium bicarbonate, grind and mix them evenly, transfer them to a tubular furnace, and carbonize them under a nitrogen atmosphere. The temperature is increased from room temperature to 700 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature is cooled to room temperature to obtain a black powder. The black powder is immersed in 150 mL of 1 mol / L hydrochloric acid solution, stirred for 10 h, filtered, washed with deionized water, and dried in a forced air drying oven at 100 °C for 24 h to obtain a high specific surface area and high nitrogen-oxygen-doped lignin porous carbon material.

[0064] Example 2 Weigh 6.9 g of nano-magnesium oxide (particle size of about 50 nm) and add it to 100 mL of deionized water. Stir and hydrolyze it at 70 °C for 4 h. After cooling it to room temperature, filter it, and then transfer the product to a 100 °C forced air drying oven and dry it for 24 h to obtain 10 g of magnesium hydroxide nanosheets. Take 10 g of alkali lignin, dissolve it in 250 mL of ethanol, add the 10 g of magnesium hydroxide nanosheets prepared above, and stir it at room temperature for 3 h to obtain a lignin / magnesium hydroxide mixed solution. 10 g of cyanuric chloride was weighed and added to the above lignin / magnesium hydroxide mixture. After reacting at 0 °C for 20 min, 7 g of melamine was added, stirred evenly at room temperature, transferred to a reactor, reacted at 140 °C for 12 h, cooled to room temperature, filtered, and then the product was transferred to a 100 °C forced air drying oven and dried for 24 h to obtain a four-component supramolecular complex of lignin / magnesium hydroxide / cyanuric acid / melamine. The composite powder was placed in a tube furnace and carbonized in a nitrogen atmosphere. The temperature was raised from room temperature to 500 °C at a heating rate of 10 °C / min and maintained for 3 h. After carbonization, the temperature was lowered to room temperature to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide composite. Weigh 1 g of nitrogen-oxygen-doped lignin carbon / magnesium oxide composite and 0.5 g of potassium acetate, grind and mix them evenly, transfer them to a tube furnace, and carbonize them under a nitrogen atmosphere. The temperature is increased from room temperature to 800 °C at a heating rate of 10 °C / min and maintained for 1 h. After carbonization, the temperature is cooled to room temperature to obtain a black powder. The black powder is immersed in 150 mL of 0.5 mol / L hydrochloric acid solution, stirred for 12 h, filtered, washed with deionized water, and dried in a forced air drying oven at 100 °C for 24 h to obtain a high specific surface area and high nitrogen-oxygen-doped lignin porous carbon material.

[0065] Example 3 Weigh 10.4 g of nano-magnesium oxide (particle size of about 50 nm) and add it to 104 mL of deionized water, stir and hydrolyze it at 75 °C for 3.5 h, filter it after cooling it to room temperature, and then transfer the product to a 100 °C forced air drying oven and dry it for 24 h to obtain 15 g of magnesium hydroxide nanosheets; take 10 g of organic solvent lignin, dissolve it in 200 mL of ethanol, add the 15 g of magnesium hydroxide nanosheets prepared above, and stir it thoroughly at room temperature for 3.5 h to obtain a lignin / magnesium hydroxide mixed solution; 12 g of cyanuric chloride was weighed and added to the above lignin / magnesium hydroxide mixture. After reacting at 0 °C for 25 min, 9 g of melamine was added, stirred evenly at room temperature, transferred to a reactor, reacted at 150 °C for 12 h, cooled to room temperature, filtered, and then the product was transferred to a 100 °C forced air drying oven and dried for 24 h to obtain a four-component supramolecular complex of lignin / magnesium hydroxide / cyanuric acid / melamine. The composite powder was placed in a tube furnace and carbonized in a nitrogen atmosphere. The temperature was raised from room temperature to 600 °C at a heating rate of 5 °C / min and maintained for 1 h. After carbonization, the temperature was lowered to room temperature to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide composite. Weigh 1 g of nitrogen-oxygen-doped lignin carbon / magnesium oxide composite and 0.75 g of potassium citrate, grind and mix them evenly, transfer them to a tube furnace, and carbonize them under a nitrogen atmosphere. The temperature is increased from room temperature to 750 °C at a heating rate of 5 °C / min and maintained for 1 h. After carbonization, the temperature is cooled to room temperature to obtain a black powder. The black powder is immersed in 150 mL of 1.5 mol / L hydrochloric acid solution, stirred for 8 h, filtered, washed with deionized water, and dried in a forced air drying oven at 100 °C for 24 h to obtain a high specific surface area and high nitrogen-oxygen-doped lignin porous carbon material.

[0066] Example 4 Weigh 17.3 g of nano-magnesium oxide (particle size of about 50 nm) and add it to 200 mL of deionized water. Stir and hydrolyze it at 85 °C for 2.5 h. After cooling to room temperature, filter it and then transfer the product to a 100 °C forced air drying oven for drying for 24 h to obtain 25 g of magnesium hydroxide nanosheets. Take 10 g of enzymatic lignin, dissolve it in 250 mL of ethanol, add the above-prepared 25 g of magnesium hydroxide nanosheets, and fully stir it at room temperature for 4.5 h to obtain a lignin / magnesium hydroxide mixed solution. 18 g of cyanuric chloride was weighed and added to the above lignin / magnesium hydroxide mixture. After reacting at 0 °C for 35 min, 12 g of melamine was added, stirred evenly at room temperature, transferred to a reactor, reacted at 170 °C for 8 h, cooled to room temperature, filtered, and then the product was transferred to a 100 °C forced air drying oven and dried for 24 h to obtain a four-component supramolecular complex of lignin / magnesium hydroxide / cyanuric acid / melamine. The composite powder was placed in a tube furnace and carbonized in a nitrogen atmosphere. The temperature was raised from room temperature to 500 °C at a heating rate of 10 °C / min and maintained for 2 h. After carbonization, the temperature was lowered to room temperature to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide composite. Weigh 1 g of nitrogen-oxygen-doped lignin carbon / magnesium oxide composite and 1.25 g of potassium bicarbonate, grind and mix them evenly, transfer them to a tube furnace, and carbonize them under a nitrogen atmosphere. The temperature is increased from room temperature to 650 °C at a heating rate of 10 °C / min and maintained for 3 h. After carbonization, the temperature is cooled to room temperature to obtain a black powder. The black powder is immersed in 150 mL of 1 mol / L hydrochloric acid solution, stirred for 10 h, filtered, washed with deionized water, and dried in a forced air drying oven at 100 °C for 24 h to obtain a high specific surface area and high nitrogen-oxygen-doped lignin porous carbon material.

[0067] Example 5 Weigh 20.7 g of nano-magnesium oxide (particle size of about 50 nm) and add it to 250 mL of deionized water. Stir and hydrolyze it at 90 °C for 2 h. After cooling to room temperature, filter it, and then transfer the product to a 100 °C forced air drying oven and dry it for 24 h to obtain 30 g of magnesium hydroxide nanosheets. Take 10 g of organic solvent lignin, dissolve it in 300 mL of ethanol, add the 30 g of magnesium hydroxide nanosheets prepared above, and stir it at room temperature for 5 h to obtain a lignin / magnesium hydroxide mixed solution. Weigh 20 g of cyanuric chloride and add it to the above lignin / magnesium hydroxide mixture, react at 0 ° C for 35 minutes, then add 15 g of melamine, stir evenly at room temperature and transfer to a reactor, react at 180 ° C for 8 hours, filter it after cooling to room temperature, and then transfer the product to a 100 ° C forced air drying oven for 24 hours to obtain a lignin / magnesium hydroxide / cyanuric acid / melamine four-component supramolecular complex; The composite powder was placed in a tube furnace and carbonized in a nitrogen atmosphere. The temperature was raised from room temperature to 600 °C at a heating rate of 5 °C / min and maintained for 1 h. After carbonization, the temperature was lowered to room temperature to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide composite. Weigh 1 g of nitrogen-oxygen-doped lignin carbon / magnesium oxide composite and 1.5 g of potassium acetate, grind and mix them evenly, transfer them to a tube furnace, and carbonize them under a nitrogen atmosphere. The temperature is increased from room temperature to 600 °C at a heating rate of 5 °C / min and maintained for 3 h. After carbonization, the temperature is cooled to room temperature to obtain a black powder. The black powder is immersed in 150 mL of 1.5 mol / L hydrochloric acid solution, stirred for 8 h, filtered, washed with deionized water, and dried in a forced air drying oven at 100 °C for 24 h to obtain a high specific surface area and high nitrogen-oxygen-doped lignin porous carbon material.

[0068] Example 6 Weigh 13.8 g of nano-magnesium oxide (particle size of about 50 nm) and add it to 200 mL of deionized water. Stir and hydrolyze it at 70 °C for 4 h. After cooling it to room temperature, filter it, and then transfer the product to a 100 °C forced air drying oven and dry it for 24 h to obtain 20 g of magnesium hydroxide nanosheets. Take 10 g of organic solvent lignin, dissolve it in 200 mL of ethanol, add 30 g of the magnesium hydroxide nanosheets prepared above, and stir it at room temperature for 5 h to obtain a lignin / magnesium hydroxide mixed solution. 15 g of cyanuric chloride was weighed and added to the above lignin / magnesium hydroxide mixture. After reacting at 0 °C for 35 min, 10 g of melamine was added, stirred evenly at room temperature, transferred to a reactor, reacted at 140 °C for 12 h, cooled to room temperature, filtered, and then the product was transferred to a 100 °C forced air drying oven and dried for 24 h to obtain a four-component supramolecular complex of lignin / magnesium hydroxide / cyanuric acid / melamine. The composite powder was placed in a tube furnace and carbonized in a nitrogen atmosphere. The temperature was raised from room temperature to 500 °C at a heating rate of 10 °C / min and maintained for 3 h. After carbonization, the temperature was lowered to room temperature to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide composite. Weigh 1 g of nitrogen-oxygen-doped lignin carbon / magnesium oxide composite and 0.5 g of potassium citrate, grind and mix them evenly, transfer them to a tube furnace, and carbonize them under a nitrogen atmosphere. The temperature is increased from room temperature to 800 °C at a heating rate of 10 °C / min and maintained for 1 h. After carbonization, the temperature is cooled to room temperature to obtain a black powder. The black powder is immersed in 150 mL of 1 mol / L hydrochloric acid solution, stirred for 10 h, filtered, washed with deionized water, and dried in a forced air drying oven at 100 °C for 24 h to obtain a high specific surface area and high nitrogen-oxygen-doped lignin porous carbon material.

[0069] Comparative Example 1 (Compared with Example 1, lignin, magnesium hydroxide, cyanuric chloride and melamine were directly physically mixed) 13.8 g of nano-magnesium oxide (particle size of about 50 nm) was weighed and added to 150 mL of deionized water, and stirred and hydrolyzed at 80 °C for 3 h. After cooling to room temperature, the mixture was filtered and then transferred to a 100 °C forced air drying oven for drying for 24 h to obtain 20 g of magnesium hydroxide nanosheets. 10 g of enzymatically hydrolyzed lignin, 20 g of magnesium hydroxide nanosheets, 15 g of cyanuric chloride and 10 g of melamine were directly ground and mixed to obtain a four-component mixture of lignin / magnesium hydroxide / cyanuric chloride / melamine. The mixture powder was placed in a tube furnace and carbonized under a nitrogen atmosphere. The temperature was increased from room temperature to 550 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature was cooled to room temperature to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide composite. Weigh 1 g of nitrogen-oxygen-doped lignin carbon / magnesium oxide composite and 1 g of potassium bicarbonate, grind and mix them evenly, transfer them to a tubular furnace, and carbonize them under a nitrogen atmosphere. The temperature is increased from room temperature to 700 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature is cooled to room temperature to obtain a black powder. The black powder is immersed in 150 mL of 1 mol / L hydrochloric acid solution, stirred for 10 h, filtered, washed with deionized water, and dried in a forced air drying oven at 100 °C for 24 h to obtain a high surface area nitrogen-oxygen-doped lignin porous carbon material.

[0070] Comparative Example 2 (Compared with Example 1, nano magnesium oxide is not hydrolyzed) Take 10 g of enzymatically hydrolyzed lignin, dissolve it in 300 mL of ethanol, add 20 g of nano-magnesium oxide powder (particle size about 50 nm), and stir it thoroughly at room temperature for 4 h to obtain a lignin / nano-magnesium oxide mixed solution; 15 g of cyanuric chloride was weighed and added to the above lignin / nano-magnesium oxide mixed solution. After reacting at 0 °C for 30 min, 10 g of melamine was added, stirred evenly at room temperature, transferred to a reactor, reacted at 160 °C for 10 h, cooled to room temperature, filtered, and then the product was transferred to a 100 °C forced air drying oven and dried for 24 h to obtain a four-component supramolecular complex of lignin / nano-magnesium oxide / cyanuric acid / melamine. The composite powder was placed in a tube furnace and carbonized in a nitrogen atmosphere. The temperature was raised from room temperature to 550 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature was lowered to room temperature to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide composite. Weigh 1 g of nitrogen-oxygen-doped lignin carbon / magnesium oxide composite and 1 g of potassium bicarbonate, grind and mix them evenly, transfer them to a tubular furnace, and carbonize them under a nitrogen atmosphere. The temperature is increased from room temperature to 700 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature is cooled to room temperature to obtain a black powder. The black powder is immersed in 150 mL of 1 mol / L hydrochloric acid solution, stirred for 10 h, filtered, washed with deionized water, and dried in a forced air drying oven at 100 °C for 24 h to obtain a nitrogen-oxygen-doped lignin porous carbon material.

[0071] Comparative Example 3 (Compared with Example 1, activation with potassium hydroxide) 13.8 g of nano-magnesium oxide (particle size of about 50 nm) was weighed and added to 150 mL of deionized water, and stirred and hydrolyzed at 80 °C for 3 h. After cooling to room temperature, the product was filtered, and then transferred to a 100 °C forced air drying oven and dried for 24 h to obtain 20 g of magnesium hydroxide nanosheets; 10 g of enzymatically hydrolyzed lignin was taken and dissolved in 300 mL of ethanol, and then 20 g of the magnesium hydroxide nanosheets prepared above were added, and the mixture was fully stirred at room temperature for 4 h to obtain a lignin / magnesium hydroxide mixed solution; 15 g of cyanuric chloride was weighed and added to the above lignin / magnesium hydroxide mixture. After reacting at 0°C for 30 min, 10 g of melamine was added, stirred evenly at room temperature, transferred to a reactor, reacted at 160°C for 10 h, cooled to room temperature, filtered, and then the product was transferred to a 100°C forced air drying oven and dried for 24 h to obtain a four-component supramolecular complex of lignin / magnesium hydroxide / cyanuric acid / melamine. The composite powder was placed in a tube furnace and carbonized in a nitrogen atmosphere. The temperature was raised from room temperature to 550 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature was lowered to room temperature to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide composite. Weigh 1 g of nitrogen-oxygen-doped lignin carbon / magnesium oxide composite and 1 g of potassium hydroxide, grind and mix them evenly, transfer them to a tube furnace, and carbonize them under a nitrogen atmosphere. The temperature is increased from room temperature to 700 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature is cooled to room temperature to obtain a black powder; the black powder is immersed in 150 mL of 1 mol / L hydrochloric acid solution, stirred for 10 h, filtered, washed with deionized water, and placed in a forced air drying oven at 100 °C for 24 h to obtain a high specific surface area and high nitrogen-oxygen-doped lignin porous carbon material.

[0072] Comparative Example 4 (Compared with Example 1, potassium bicarbonate activation was not used) Weigh 13.8 g of nano-magnesium oxide (particle size of about 50 nm) and add it to 150 mL of deionized water. Stir and hydrolyze it at 80 °C for 3 h. After cooling to room temperature, filter it and then transfer the product to a 100 °C forced air drying oven for 24 h to obtain 20 g of magnesium hydroxide nanosheets. Take 10 g of enzymatic lignin, dissolve it in 300 mL of ethanol, add the above-prepared 20 g of magnesium hydroxide nanosheets, and stir it at room temperature for 4 h to obtain a lignin / magnesium hydroxide mixed solution. 15 g of cyanuric chloride was weighed and added to the above lignin / magnesium hydroxide mixture, reacted at 0 °C for 30 min, and then 10 g of melamine was added. After stirring at room temperature for 10 h, the mixture was transferred to a reactor and reacted at 160 °C for 10 h. After cooling to room temperature, the mixture was filtered and then the product was transferred to a 100 °C forced air drying oven and dried for 24 h to obtain a four-component supramolecular complex of lignin / magnesium hydroxide / cyanuric acid / melamine. The composite powder was placed in a tube furnace and carbonized in a nitrogen atmosphere. The temperature was raised from room temperature to 550 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature was lowered to room temperature to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide composite. Weigh 1 g of nitrogen-oxygen-doped lignin carbon / magnesium oxide composite, transfer it to a tube furnace, and carbonize it under a nitrogen atmosphere. The temperature is increased from room temperature to 700 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature is cooled to room temperature to obtain a black powder. The black powder is immersed in 150 mL of 1 mol / L hydrochloric acid solution, stirred for 10 h, filtered, washed with deionized water, and dried in a forced air drying oven at 100 °C for 24 h to obtain a nitrogen-oxygen-doped lignin porous carbon material.

[0073] Comparative Example 5 (Compared with Example 1, without solvent thermal reaction) Weigh 13.8 g of nano-magnesium oxide (particle size of about 50 nm) and add it to 150 mL of deionized water. Stir and hydrolyze it at 80 °C for 3 h. After cooling to room temperature, filter it and then transfer the product to a 100 °C forced air drying oven for 24 h to obtain 20 g of magnesium hydroxide nanosheets. Take 10 g of enzymatic lignin, dissolve it in 300 mL of ethanol, add the above-prepared 20 g of magnesium hydroxide nanosheets, and stir it at room temperature for 4 h to obtain a lignin / magnesium hydroxide mixed solution. Weigh 15 g of cyanuric chloride and add it to the above lignin / magnesium hydroxide mixture, react at 0°C for 30 min, then add 10 g of melamine, stir evenly at room temperature, transfer to a 100°C forced air drying oven and dry for 24 h to obtain a lignin / magnesium hydroxide / cyanuric acid / melamine composite; The composite powder was placed in a tube furnace and carbonized in a nitrogen atmosphere. The temperature was raised from room temperature to 550 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature was lowered to room temperature to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide composite. Weigh 1 g of nitrogen-oxygen-doped lignin carbon / magnesium oxide composite and 1 g of potassium bicarbonate, grind and mix them evenly, transfer them to a tubular furnace, and carbonize them under a nitrogen atmosphere. The temperature is increased from room temperature to 700 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature is cooled to room temperature to obtain a black powder. The black powder is immersed in 150 mL of 1 mol / L hydrochloric acid solution, stirred for 10 h, filtered, washed with deionized water, and dried in a forced air drying oven at 100 °C for 24 h to obtain a nitrogen-oxygen-doped lignin porous carbon material.

[0074] Comparative Example 6 (Compared with Example 1, cyanuric chloride was not used to modify lignin, and cyanuric acid and melamine were directly added to carry out solvent thermal reaction) 13.8 g of nano-magnesium oxide (particle size of about 50 nm) was weighed and added to 150 mL of deionized water, and stirred and hydrolyzed at 80 °C for 3 h. After cooling to room temperature, the product was filtered, and then transferred to a 100 °C forced air drying oven and dried for 24 h to obtain 20 g of magnesium hydroxide nanosheets; 10 g of enzymatically hydrolyzed lignin was taken and dissolved in 300 mL of ethanol, and then 20 g of the magnesium hydroxide nanosheets prepared above were added, and the mixture was fully stirred at room temperature for 4 h to obtain a lignin / magnesium hydroxide mixed solution; 15 g of cyanuric acid and 10 g of melamine were weighed and added to the above lignin / magnesium hydroxide mixture, stirred evenly at room temperature, and then transferred to a reactor, reacted at 160 ° C for 10 h, cooled to room temperature, filtered, and then the product was transferred to a 100 ° C forced air drying oven and dried for 24 h to obtain a lignin / magnesium hydroxide / cyanuric acid / melamine four-component supramolecular complex; The composite powder was placed in a tube furnace and carbonized in a nitrogen atmosphere. The temperature was raised from room temperature to 550 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature was lowered to room temperature to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide composite. Weigh 1 g of nitrogen-oxygen-doped lignin carbon / magnesium oxide composite and 1 g of potassium bicarbonate, grind and mix them evenly, transfer them to a tubular furnace, and carbonize them under a nitrogen atmosphere. The temperature is increased from room temperature to 700 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature is cooled to room temperature to obtain a black powder. The black powder is immersed in 150 mL of 1 mol / L hydrochloric acid solution, stirred for 10 h, filtered, washed with deionized water, and dried in a forced air drying oven at 100 °C for 24 h to obtain a nitrogen-oxygen-doped lignin porous carbon material.

[0075] Comparative Example 7 (Compared with Example 1, deionized water was used as the solvent) Weigh 13.8 g of nano-magnesium oxide (particle size of about 50 nm) and add it to 150 mL of deionized water. Stir and hydrolyze it at 80 °C for 3 h. After cooling to room temperature, filter it, and then transfer the product to a 100 °C forced air drying oven and dry it for 24 h to obtain 20 g of magnesium hydroxide nanosheets. Take 10 g of enzymatic lignin, dissolve it in 300 mL of deionized water, add the above-prepared 20 g of magnesium hydroxide nanosheets, and stir it at room temperature for 4 h to obtain a lignin / magnesium hydroxide mixed solution. Weigh 15 g of cyanuric chloride and add it to the above lignin / magnesium hydroxide mixture, react at 0 ° C for 30 minutes, then add 10 g of melamine, stir evenly at room temperature and transfer to a reactor, react at 160 ° C for 10 hours, filter after cooling to room temperature, and then transfer the product to a 100 ° C forced air drying oven for 24 hours to obtain a lignin / magnesium hydroxide / cyanuric acid / melamine four-component composite; The composite powder was placed in a tube furnace and carbonized in a nitrogen atmosphere. The temperature was raised from room temperature to 550 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature was lowered to room temperature to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide composite. Weigh 1 g of nitrogen-oxygen-doped lignin carbon / magnesium oxide composite and 1 g of potassium bicarbonate, grind and mix them evenly, transfer them to a tubular furnace, and carbonize them under a nitrogen atmosphere. The temperature is increased from room temperature to 700 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature is cooled to room temperature to obtain a black powder. The black powder is immersed in 150 mL of 1 mol / L hydrochloric acid solution, stirred for 10 h, filtered, washed with deionized water, and dried in a forced air drying oven at 100 °C for 24 h to obtain a high specific surface area and high nitrogen-oxygen-doped lignin porous carbon material.

[0076] Comparative Example 8 (Compared with Example 1, without adding cyanuric chloride) 13.8 g of nano-magnesium oxide (particle size of about 50 nm) was weighed and added to 150 mL of deionized water, and stirred and hydrolyzed at 80 °C for 3 h. After cooling to room temperature, the product was filtered, and then transferred to a 100 °C forced air drying oven and dried for 24 h to obtain 20 g of magnesium hydroxide nanosheets; 10 g of enzymatically hydrolyzed lignin was taken and dissolved in 300 mL of ethanol, and then 20 g of the magnesium hydroxide nanosheets prepared above were added, and the mixture was fully stirred at room temperature for 4 h to obtain a lignin / magnesium hydroxide mixed solution; Weigh 10 g of melamine and add it to the above lignin / magnesium hydroxide mixed solution, stir it evenly at room temperature, transfer it to a reactor, react it at 160 ° C for 10 h, filter it after cooling it to room temperature, and then transfer the product to a 100 ° C forced air drying oven and dry it for 24 h to obtain a lignin / magnesium hydroxide / melamine composite; The composite powder was placed in a tube furnace and carbonized in a nitrogen atmosphere. The temperature was raised from room temperature to 550 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature was lowered to room temperature to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide composite. Weigh 1 g of nitrogen-oxygen-doped lignin carbon / magnesium oxide composite and 1 g of potassium bicarbonate, grind and mix them evenly, transfer them to a tubular furnace, and carbonize them under a nitrogen atmosphere. The temperature is increased from room temperature to 700 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature is cooled to room temperature to obtain a black powder. The black powder is immersed in 150 mL of 1 mol / L hydrochloric acid solution, stirred for 10 h, filtered, washed with deionized water, and dried in a forced air drying oven at 100 °C for 24 h to obtain a nitrogen-oxygen-doped lignin porous carbon material.

[0077] Comparative Example 9 (Compared with Example 1, without adding melamine) 13.8 g of nano-magnesium oxide (particle size of about 50 nm) was weighed and added to 150 mL of deionized water, and stirred and hydrolyzed at 80 °C for 3 h. After cooling to room temperature, the product was filtered, and then transferred to a 100 °C forced air drying oven and dried for 24 h to obtain 20 g of magnesium hydroxide nanosheets; 10 g of enzymatically hydrolyzed lignin was taken and dissolved in 300 mL of ethanol, and then 20 g of the magnesium hydroxide nanosheets prepared above were added, and the mixture was fully stirred at room temperature for 4 h to obtain a lignin / magnesium hydroxide mixed solution; Weigh 15 g of cyanuric chloride and add it to the above lignin / magnesium hydroxide mixed solution, react at 0°C for 30 minutes, stir evenly at room temperature and transfer to a reactor, react at 160°C for 10 hours, filter after cooling to room temperature, and then transfer the product to a 100°C forced air drying oven for drying for 24 hours to obtain a lignin / magnesium hydroxide / cyanuric acid complex; The composite powder was placed in a tube furnace and carbonized in a nitrogen atmosphere. The temperature was raised from room temperature to 550 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature was lowered to room temperature to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide composite. Weigh 1 g of nitrogen-oxygen-doped lignin carbon / magnesium oxide composite and 1 g of potassium bicarbonate, grind and mix them evenly, transfer them to a tubular furnace, and carbonize them under a nitrogen atmosphere. The temperature is increased from room temperature to 700 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature is cooled to room temperature to obtain a black powder. The black powder is immersed in 150 mL of 1 mol / L hydrochloric acid solution, stirred for 10 h, filtered, washed with deionized water, and dried in a forced air drying oven at 100 °C for 24 h to obtain a nitrogen-oxygen-doped lignin porous carbon material.

[0078] Comparative Example 10 (Compared with Example 1, without adding cyanuric chloride and melamine) 13.8 g of nano-magnesium oxide (particle size of about 50 nm) was weighed and added to 150 mL of deionized water, and stirred and hydrolyzed at 80 °C for 3 h. After cooling to room temperature, the product was filtered, and then transferred to a 100 °C forced air drying oven and dried for 24 h to obtain 20 g of magnesium hydroxide nanosheets; 10 g of enzymatically hydrolyzed lignin was taken and dissolved in 300 mL of ethanol, and then 20 g of the magnesium hydroxide nanosheets prepared above were added, and the mixture was fully stirred at room temperature for 4 h to obtain a lignin / magnesium hydroxide mixed solution; The mixed solution was transferred to a reactor and reacted at 160 °C for 10 h. After cooling to room temperature, the mixture was filtered and then the product was transferred to a 100 °C forced air drying oven and dried for 24 h to obtain a lignin / magnesium hydroxide complex. The composite powder was placed in a tube furnace and carbonized under a nitrogen atmosphere. The temperature was increased from room temperature to 550 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature was cooled to room temperature to obtain an oxygen-doped lignin carbon / magnesium oxide composite. Weigh 1 g of nitrogen-oxygen-doped lignin carbon / magnesium oxide composite and 1 g of potassium bicarbonate, grind and mix them evenly, transfer them to a tubular furnace, and carbonize them under a nitrogen atmosphere. The temperature is increased from room temperature to 700 °C at a heating rate of 5 °C / min and maintained for 2 h. After carbonization, the temperature is cooled to room temperature to obtain a black powder. The black powder is immersed in 150 mL of 1 mol / L hydrochloric acid solution, stirred for 10 h, filtered, washed with deionized water, and dried in a forced air drying oven at 100 °C for 24 h to obtain an oxygen-doped lignin porous carbon material.

[0079] Results and Analysis: The structure of the lignin carbon material obtained in the embodiment and the comparative example was characterized and its performance as the positive electrode material of the zinc ion hybrid capacitor electrode was tested. The results are shown in Tables 1 and Figures 1 to 5 .

[0080] The microscopic morphology and structure of the samples of the present invention were characterized by scanning electron microscopy (SEM, HITACHI SU8220) and high-resolution field emission transmission electron microscopy (TEM, JEOL JEM-2100F). The functional groups of the samples were characterized by Fourier transform infrared spectroscopy (FT-IR, Thermo Nicolet iS10). The specific surface area and pore structure of the samples were tested using a fully automatic specific surface and porosity analyzer (Micromeritics ASAP 2020 instrument).

[0081] In the performance test of the zinc ion hybrid capacitor electrode, the lignin carbon material obtained by the present invention, acetylene black and polytetrafluoroethylene were mixed in a mass ratio of 8:1:1 and rolled on a stainless steel mesh as the positive electrode material of the zinc ion hybrid capacitor. Metallic zinc was directly used as the negative electrode, 2 mol / L zinc sulfate was used as the electrolyte, and Whatman glass fiber was used as the diaphragm. The electrochemical performance test was carried out using an electrochemical workstation (Bio-Logic VMP-3e), with a voltage window of 0.2-1.8 V and a current density of 0.1 A / g and 10 A / g.

[0082] Table 1 shows the electrochemical properties of the pore structure parameters of the lignin porous carbon materials prepared in different embodiments and comparative examples.

[0083] Table 1 Surface element content and pore structure characteristic parameters of lignin porous carbon materials Table 1 Description: The specific surface areas of the nitrogen-oxygen doped lignin porous carbon materials prepared in Examples 1 to 6 all exceeded 2500 m 2 / g, the proportion of micropores is greater than 85% (the proportion of mesopores is greater than 43%; the proportion of micropores is greater than 40%), and the total nitrogen and oxygen content on the surface of the carbon material is greater than 13 at.% (the oxygen content is greater than 8.0 at.%, and the nitrogen content is greater than 5.0 at.%). The specific surface area of ​​Example 1 is as high as 2848 m 2 / g, the microporosity is 44.2%, the mesoporosity is 44.8%, the micro-mesopore ratio is 89%, the oxygen content is 8.9 at.%, the nitrogen content is 5.4 at.%, and the sum of the nitrogen and oxygen contents is 14.3 at.%, which is significantly higher than the nitrogen-oxygen doped lignin porous carbon material prepared by direct physical mixing in Comparative Example 1. The electrochemical performance test results of the assembled zinc ion hybrid capacitor show that the specific capacitance of the nitrogen-oxygen doped lignin porous carbon material prepared in Example 1 is 433F / g at a current density of 0.1 A / g, and the specific capacitance is 216F / g at a current density of 10 A / g, which is higher than the nitrogen-oxygen doped lignin porous carbon material prepared in Comparative Example 1. It shows that the high specific surface area and high nitrogen-oxygen doped lignin porous carbon material prepared by the technology of the present invention is better than the nitrogen-oxygen doped lignin porous carbon material prepared by direct physical mixing.

[0084] Compared with Example 1, the nano-magnesium oxide in Comparative Example 2 was not hydrolyzed, and the hydroxyl groups on the surface of magnesium oxide were less, resulting in poor compatibility between lignin and the template, and failure to form a uniform lignin / magnesium oxide composite, which weakened the structural guidance effect of the magnesium oxide template, and the unhydrolyzed nano-magnesium oxide had no nano-sheet structure. Therefore, the mesopores formed by lignin during the pyrolysis and carbonization process were less (28.5%), and the specific surface area was low (2216 m 2 / g) and structural disorder, resulting in a low specific capacitance (318 F / g) of the zinc-ion hybrid capacitor.

[0085] Compared with Example 1, Comparative Example 3 was activated by potassium hydroxide, a strong corrosive activator, to form a developed pore structure with a microporosity of 49.5% and a specific surface area of ​​2364 m 2 / g. However, due to the strong corrosiveness of potassium hydroxide and excessive activation, the prepared lignin carbon material has low mesopores (27.9%), low ion transfer rate, serious loss of nitrogen and oxygen species (nitrogen and oxygen content is only 9.5 at.%), and poor interface wettability, resulting in the specific capacitance of the assembled zinc ion hybrid capacitor being 301 F / g.

[0086] Compared with Example 1, Comparative Example 4 did not use weakly corrosive potassium salt for activation and pore formation, and the prepared lignin porous carbon material had a higher nitrogen and oxygen content (nitrogen content: 12.1 at.%, oxygen content 8.8 at.%) and mesoporosity (69.4%). However, without further activation and pore formation, the microporosity of the lignin porous carbon material was as low as 3.4%, and the specific surface area was only 876 m 2 / g, and the lack of active sites for zinc storage leads to the poor electrochemical performance of zinc-ion hybrid capacitors (185 F / g).

[0087] Compared with Example 1, Comparative Example 5 did not use solvent thermal reaction condensation to form supramolecules. Cyanuric acid and melamine had poor thermal stability during pyrolysis and carbonization, and nitrogen-containing species were seriously lost during the subsequent activation process. The prepared lignin porous carbon material had a low nitrogen and oxygen content (nitrogen content: 1.5 at.%, oxygen content: 8.0 at.%), resulting in poor carbon interface wettability, inaccessible zinc storage active sites, lack of pseudocapacitive active sites, and a specific capacitance of the zinc ion hybrid capacitor of 287 F / g Compared with Example 1, Comparative Example 6 did not use cyanuric chloride to modify lignin, but directly added cyanuric acid and melamine into the reaction system, and prepared a four-component mixture of lignin / magnesium hydroxide / cyanuric acid / melamine by solvothermal reaction. Due to the weak physical interaction (hydrogen bond and van der Waals force, etc.) between lignin and the nitrogen source, and the low content of the nitrogen source compared to lignin, the nitrogen species were seriously lost during the carbonization activation process, and the nitrogen content was only 1.7 at.%, and the specific capacitance of the assembled zinc ion hybrid capacitor was 295 F / g.

[0088] Compared with Example 1, Comparative Example 7 uses deionized water as the solvent. The solubility of lignin in deionized water is low, resulting in uneven composite of lignin and magnesium hydroxide template. The prepared carbon material has fewer mesopores (20.5%) and a lower specific surface area (1987 m 2 / g). And because the intermolecular forces of lignin in water are strong and seriously aggregated, the oxygen-containing functional groups such as hydroxyl groups cannot be fully exposed, resulting in low reactivity of lignin with cyanuric chloride. Lignin cannot fully participate in the construction of supramolecules, and nitrogen species are seriously lost during the carbonization and activation process, with a nitrogen content of only 1.9 at.%. Therefore, the prepared nitrogen-oxygen doped lignin porous carbon material has a disordered nanostructure, fewer mesopores, and a low nitrogen-oxygen content (9.6 at.%), resulting in a specific capacitance of the assembled zinc ion hybrid capacitor of 279 F / g.

[0089] Compared with Example 1, Comparative Examples 8 to 10 did not use cyanuric chloride to modify lignin and / or did not add melamine, resulting in the failure to form a four-component supramolecular complex. Therefore, the thermal stability of nitrogen species is poor, and the loss is serious during the activation process. The nitrogen content of the prepared nitrogen-oxygen doped lignin porous carbon materials is less than 1.0 at.%, and the electrochemical performance of the zinc ion hybrid capacitor is poor, which proves the importance of cyanuric chloride and melamine in the nitrogen doping process in the present invention.

[0090] In summary, the lignin described in the method of the present invention assembles a four-component supramolecular complex through hydrogen bonds and chemical bonds, and can prepare a high specific surface area and high nitrogen and oxygen-doped lignin porous carbon material after carbonization and activation. As the positive electrode material of the zinc ion hybrid capacitor, it exhibits excellent specific capacitance, which is better than the nitrogen and oxygen-doped lignin porous carbon materials prepared in Comparative Examples 1 to 10.

[0091] Figure 1 is the Fourier transform infrared spectrum of lignin-cyanuric acid obtained by modifying lignin with cyanuric chloride in Example 1 of the present invention, at 850 cm -1 The C-Cl stretching vibration absorption peak disappears at 1025 cm -1 The enhancement of the COC absorption peak at 4° indicated that cyanuric chloride was successfully grafted onto the lignin molecules.

[0092] Figure 2 This is a scanning electron microscope image of the nitrogen-oxygen doped lignin porous carbon material obtained in Example 1 of the present invention. It can be seen that it is composed of interconnected and staggered two-dimensional nanosheets and has an open and interconnected pore structure.

[0093] Figure 3 This is a transmission electron microscope picture of the nitrogen-oxygen doped lignin porous carbon material obtained in Example 1 of the present invention. It can be seen that it is composed of a rich nanosheet structure and has a large number of nanopores.

[0094] Figure 4 It is the nitrogen adsorption / desorption isotherm and pore size distribution curve of the nitrogen-oxygen doped lignin porous carbon material obtained in Example 1 of the present invention. The nitrogen adsorption / desorption curve shows the characteristics of a type IV adsorption / desorption curve, and an H-4 type hysteresis loop appears in the high pressure region, proving that the prepared carbon material has a hierarchical pore structure dominated by micro-mesopores. The pore size distribution diagram shows that its micropores are concentrated around 0.46, 0.80, and 1.18 nm, and the mesopores are distributed around 3.18 nm. The rich microporous structure is attributed to the activation of mesoporous magnesium oxide produced by the decomposition of magnesium hydroxide and weakly corrosive potassium salts.

[0095] Figure 5 This is the constant current charge-discharge curve of the nitrogen-oxygen doped lignin porous carbon material obtained in Example 1 of the present invention. The figure shows that the curve shape of the prepared carbon material at different current densities is similar to an isosceles triangle, proving that it has typical double-layer capacitance characteristics and high reversibility.

[0096] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a high specific surface area high nitrogen and oxygen doped lignin porous carbon material, characterized in that: The following steps are involved: (1) dissolving lignin in ethanol, adding magnesium hydroxide nanosheets, and stirring to obtain a lignin / magnesium hydroxide mixed solution; (2) adding an excess of cyanuric chloride to the lignin / magnesium hydroxide mixture to react, then adding melamine to carry out a solvothermal reaction, filtering and drying to obtain a four-component supramolecular complex of lignin / magnesium hydroxide / cyanuric acid / melamine; (3) carbonizing the four-component supramolecular complex of lignin / magnesium hydroxide / cyanuric acid / melamine under an inert gas atmosphere to obtain a nitrogen-oxygen doped lignin carbon / magnesium oxide complex; (4) After the nitrogen-oxygen doped lignin carbon / magnesium oxide composite and the weakly corrosive potassium salt are evenly mixed, the mixture is activated in an inert gas atmosphere, acid-washed, filtered and dried to obtain a high specific surface area and high nitrogen-oxygen doped lignin porous carbon material.

2. The method for preparing a high specific surface area high nitrogen and oxygen doped lignin porous carbon material according to claim 1, characterized in that: The ratio of lignin, ethanol and magnesium hydroxide nanosheets in step (1) is 10 g: 200-300 mL: 10-30 g; The mass ratio of the cyanuric chloride and melamine in step (2) to the lignin in step (1) is 10-20:5-15:10; The lignin in step (1) is at least one of enzymatic lignin produced as a byproduct of the bioethanol industry, alkali lignin in black liquor from alkaline pulping, and organic solvent lignin; The temperature for reacting the cyanuric chloride in step (2) is 0 to 5°C and the reaction time is 20 to 40 minutes; The temperature of adding melamine to carry out the solvothermal reaction in step (2) is 140-180° C. and the time is 8-12 h.

3. The method for preparing a high specific surface area high nitrogen and oxygen doped lignin porous carbon material according to claim 2, characterized in that: The ratio of lignin, ethanol and magnesium hydroxide nanosheets in step (1) is 10 g: 200-300 mL: 10-20 g; The mass ratio of the cyanuric chloride and melamine in step (2) to the lignin in step (1) is 10-20:7-15:10; The temperature for reacting the cyanuric chloride in step (2) is 0 to 5°C and the reaction time is 20 to 30 minutes; The temperature for the solvent thermal reaction of adding melamine in step (2) is 140-160° C. and the time is 10-12 hours.

4. The method for preparing a high specific surface area high nitrogen and oxygen doped lignin porous carbon material according to claim 1, characterized in that: The weakly corrosive potassium salt in step (4) is at least one of potassium bicarbonate, potassium acetate and potassium citrate; In step (4), the mass ratio of the nitrogen-oxygen doped lignin carbon / magnesium oxide composite to the weakly corrosive potassium salt is 1:0.5-1.

5.

5. The method for preparing a high specific surface area high nitrogen and oxygen doped lignin porous carbon material according to claim 4, characterized in that: In step (4), the mass ratio of the nitrogen-oxygen doped lignin carbon / magnesium oxide composite to the weakly corrosive potassium salt is 1:0.5-1.

6. The method for preparing a high specific surface area high nitrogen and oxygen doped lignin porous carbon material according to claim 1, characterized in that: The carbonization temperature in step (3) is 500-600°C and the time is 1-3 hours; The activation temperature in step (4) is 600-800°C and the activation time is 1-3 h; The activation heating rates in steps (3) and (4) are both 5 to 10 °C / min; The inert gas in steps (3) and (4) is at least one of a rare gas and nitrogen; The acid solution used for pickling in step (4) is one of a 0.5-1.5 mol / L hydrochloric acid solution or a sulfuric acid solution, and the soaking and washing time is 8-12 h.

7. The method for preparing a high specific surface area high nitrogen and oxygen doped lignin porous carbon material according to claim 6, characterized in that: The carbonization temperature in step (3) is 550-600°C and the time is 1-2 h; The activation temperature in step (4) is 700-800°C and the activation time is 1-2 h.

8. The method for preparing a high specific surface area high nitrogen and oxygen doped lignin porous carbon material according to claim 1, characterized in that: The magnesium hydroxide nanosheets in step (1) are obtained by the following method: dispersing nano-magnesium oxide in water, heating and hydrolyzing, filtering and drying to obtain magnesium hydroxide nanosheets; The particle size of the nano magnesium oxide is 10 to 100 nm; The heating hydrolysis temperature is 70-90°C and the time is 2-4 hours.

9. A high specific surface area and high nitrogen and oxygen doped lignin porous carbon material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the high specific surface area and high nitrogen and oxygen doped lignin porous carbon material as claimed in claim 9 in zinc ion hybrid capacitors.

Citation Information

Patent Citations

  • Supramolecular induced nitrogen-doped lignin derived carbon material as well as preparation method and application thereof

    CN115215320A

  • High-mesoporous-rate nitrogen and sulfur double-doped lignin-based carbon material as well as preparation and application thereof

    CN116199206A

  • Crop straw-based nitrogen-doped porous carbon material preparation method and application thereof

    WO2022052539A1

Cited By

  • Preparation method of lignin-based three-dimensional flaky carbon material

    CN120878469A

  • Biochar-loaded zinc-iron layered bimetallic oxide composite material as well as preparation method and application thereof

    CN122252161A

  • Control method for nitrogen-oxygen modification synergistic reinforcement of H2S adsorption activated carbon

    CN122501866A